J-GEM optical and near-infrared follow-up of gravitational wave events during LIGO's and Virgo's third observing run. (28th January 2021) - Sasada, Mahito; Utsumi, Yousuke; Itoh, Ryosuke; Tominaga, Nozomu; Tanaka, Masaomi; Morokuma, Tomoki; Yanagisawa, Kenshi; Kawabata, Koji S; Ohgami, Takayuki; Yoshida, Michitoshi; Abe, Fumio; Adachi, Ryo; et al.
Abstract: The Laser Interferometer Gravitational-wave Observatory Scientific Collaboration and Virgo Collaboration (LVC) sent out 56 gravitational-wave (GW) notices during the third observing run (O3). The Japanese Collaboration for Gravitational wave ElectroMagnetic follow-up (J-GEM) performed optical and near-infrared observations to identify and observe an electromagnetic (EM) counterpart. We constructed a web-based system that enabled us to obtain and share information on candidate host galaxies for the counterpart, and the status of our observations. Candidate host galaxies were selected from the GLADE catalog with a weight based on the 3D GW localization map provided by LVC. We conducted galaxy-targeted and wide-field blind surveys, real-time data analysis, and visual inspection of observed galaxies. We performed galaxy-targeted follow-ups to 23 GW events during O3, and the maximum probability covered by our observations reached 9.8% . Among these, we successfully started observations for 10 GW events within 0.5 days after the detection. This result demonstrates that our follow-up observation has the potential to constrain EM radiation models for a merger of binary neutron stars at a distance of up to 100 Mpc with a probability area of ≤ 500 deg^2 .